ChemInform Abstract: Organocatalytic Asymmetric Reaction of Indol‐2‐yl Carbinols with Enamides: Synthesis of Chiral 2‐Indole‐Substituted 1, 1‐Diarylalkanes. Issue 46 (November 2015) - Liu, Chao‐You; Han, Fu‐She
Abstract The title reaction is applicable to a wide variety of indol‐2‐yl carbinols and various enamides.